Phoenix Media Stock Price Forecasting: Econometric Case Study - Yang, Jiming; Lyu, Wenbo (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
With the rapid development of information technology and the high openness of financial markets, investment activities have become more complex and diversified. In this complex and changeable investment environment, predicting the rise and fall of stock prices has become one of the important tasks of investors and financial institutions. However, the volatility and uncertainty of the stock market make the stock price prediction unusually difficult. This paper aims to empirically analyze the prediction of the rise and fall of Phoenix Media stock through the analysis method based on the random forest model. In this study, we developed a random forest model and trained and optimized the historical Phoenix Media stock data, and then applied the model to the new data set to predict the rise and fall of Phoenix Media stock. The effectiveness and performance of the random forest model in predicting Phoenix Media stock are verified by evaluating the accuracy and stability of its prediction results and comparing them with those of traditional stock prediction methods. This study aims to make contributions from both aspects of theoretical and practical application. The structure of the article first outlines the background and objectives of the research and clarifies its value to relevant academic fields at home and abroad. Subsequently, the study conducted an in-depth system requirements analysis to clarify the requirements of the system. Then, the development environment and the tools selected were described in detail, and four key modules were successfully realized, including data preprocessing, random forest model construction, model training and verification, and prediction results presentation. In the conclusions, the study objectives, implementation steps and challenges were reviewed, and corresponding conclusions were drawn. After empirical analysis, the method based on the random forest model has certain accuracy and reliability for the rise and fall prediction of Phoenix Media stock, which provides a valuable reference for research in this field.